The effects of raw material particles size, types of solvents and solvent-to-solid ratio on the yield of rotenone extracted from derris elliptica roots - Saiful Irwan Zubairi; Mohamad Roji Sarmidi; Ramlan Abdul Aziz (Universiti Kebangsaan Malaysia, 2014)
Currently, bio-pesticide is relatively harmless to human and environment and thus desirable for its use in the control of insect vectors. Bio-pesticide has been increasingly important in both scale commercial agriculture and small plot, subsistence farming. One of the sources for bio-pesticide is ‘tuba’ plant, known as Derris elliptica. Derris elliptica contains bio-active compounds known as rotenone (C23H33O6) which is harmless to plants, highly toxic to many insects and relatively innocuous to mammals. The study was carried out to investigate the appropriate processing parameters with the aimed to acquire high yield of rotenone (mg) and concentration (mg/mL) of the exhaustive extraction process by evaluating the kinetics of the normal soaking extraction (NSE) method. The raw plants were collected from Kota Johor Lama, Johor and sorted to collect the root. The roots were sorted into 2 types of raw material particles size (mm in diameter) prior to the extraction process. Rotenone from the root part was extracted by using a NSE method at ambient temperature of 27±1oC. Three types of solvents and 2 solvent-to-solid ratios were utilized throughout the extraction process. The extraction was carried out for 50 h and the fractions of the liquid crude extract were collected for each interval time (2 h/mL/fraction) and further cleaned up to remove any fine debris prior to the determination of rotenone content (mg) and its concentration (mg/mL) via reverse-phase high performance liquid chromatography (RP-HPLC). From the kinetics result obtained, it was found that the fine Derris elliptica roots with particles size of 0.5 - 2 mm in diameter and solvent-to-solid ratio of 10 mL/g of acetone solvent system were considered the best processing parameters to procure high yield of rotenone and its concentration.